Seismic Investigations at the Ketzin CO2 Injection Site, Germany: Applications to Subsurface Feature Mapping and CO2 Seismic Response Modeling - Kazemeini, Sayed Hesammoddin (Uppsala universitet, Geofysik, 2009)
3D seismic data are widely used for many different purposes. Despite different objectives, a common goal in almost all 3D seismic programs is to attain better understanding of the subsurface features. In gas injection projects, which are mainly for Enhanced Oil Recovery (EOR) and recently for environmental purposes, seismic data have an important role in the gas monitoring phase. This thesis deals with a 3D seismic investigation at the CO2 injection site at Ketzin, Germany. I focus on two critical aspects of the project: the internal architecture of the heterogeneous Stuttgart reservoir and the detectability of the CO2 response from surface seismic data. Conventional seismic methods are not able to conclusively map the internal reservoir architecture due to their limited seismic resolution. In order to overcome this limitation, I use the Continuous Wavelet Transform (CWT) decomposition technique, which provides frequency spectra with high temporal resolution without the disadvantages of the windowing process associated with the other techniques. Results from applying this technique reveal more of the details of sand bodies within the Stuttgart Formation. The CWT technique also helps to detect and map remnant gas on the top of the structure. In addition to this method, I also show that the pre-stack spectral blueing method, which is presented for the first time in this research, has an ability to enhance seismic resolution with fewer artifacts in comparison with the post-stack spectral blueing method. The second objective of this research is to evaluate the CO2 response on surface seismic data as a feasibility study for CO2 monitoring. I build a rock physics model to estimate changes in elastic properties and seismic velocities caused by injected CO2. Based on this model, I study the seismic responses for different CO2 injection geometries and saturations using one dimensional (1D) elastic modeling and two dimensional (2D) acoustic finite-difference modeling. Results show that, in spite of random and coherent noises and reservoir heterogeneity, the CO2 seismic response should be strong enough to be detectable on surface seismic data. I use a similarity-based image registration method to isolate amplitude changes due to the reservoir from amplitude changes caused by time shifts below the reservoir. In support of seismic monitoring using surface seismic data, I also show that acoustic impedance versus Poisson’s ratio cross-plot is a suitable attribute for distinguishing gas-bearing sands from brine-bearing sands. === CO2SINK Project